2000
DOI: 10.1515/jbcpp.2000.11.3.215
|View full text |Cite
|
Sign up to set email alerts
|

The Varieties of Auditory Neuropathy

Abstract: Auditory neuropathy (AN) was initially described as impairment of auditory neural function, with preserved cochlear hair cell function. In this report, 67 patients with audiological and neurophysiological criteria for hearing loss due to auditory neuropathy are described. Reviewing this large body of patients, AN appears to consist of a number of varieties, with different etiologies and sites affected. All varieties share a relatively spared receptor function, and an impaired neural response, with diminished a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
215
1
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(245 citation statements)
references
References 29 publications
10
215
1
14
Order By: Relevance
“…The level of significance was set at p < 0.05 for all tests. Table 1 contains clinical, audiological, and neurological data from the eight AN patients ordered according to etiology which is diverse in AN (Starr et al, 2000). The disorder was genetic in three (#1-3), degenerative in one (#4), immunological in three (#5-7), and congenital in one (#8).…”
Section: Statistical Evaluationmentioning
confidence: 99%
“…The level of significance was set at p < 0.05 for all tests. Table 1 contains clinical, audiological, and neurological data from the eight AN patients ordered according to etiology which is diverse in AN (Starr et al, 2000). The disorder was genetic in three (#1-3), degenerative in one (#4), immunological in three (#5-7), and congenital in one (#8).…”
Section: Statistical Evaluationmentioning
confidence: 99%
“…The preservation of otoacoustic emissions suggests that outer hair cells function normally. Therefore, the sites of cellular disorders are either in the inner hair cells, SG neurons, central auditory centers, or a combination of these sites (Starr et al, 2000). Genetic, as well as toxic and metabolic factors (e.g., anoxia, hyperbilirubinemia), are suspected contributing factors to auditory neuropathy.…”
Section: Cx29mentioning
confidence: 99%
“…Comparison of results from these two tests has revealed that a subset of sensorineural hearing impairments arise despite apparently normal function of the outer hair cells, as implied by intact OAE responses despite absent or greatly attenuated ABRs. This clinical condition has been termed auditory neuropathy (AN;Starr et al 1996Starr et al , 2000, even though it could logically arise from either damage/degeneration of the cochlear nerve or selective damage/degeneration of the inner hair cells, which provide the exclusive synaptic drive to 95% of the cochlear nerve fibers (Spoendlin 1972). Depending on the size and nature of the population sampled, estimates of the prevalence of AN range anywhere from 5% to 15% of those with sensorineural hearing loss (Rance et al 1999;D'Agostino and Austin 2004).…”
Section: Introductionmentioning
confidence: 99%